Activities experience activities of small students in elementary schools in Thuy Nguyen District, Hai Phong City by access to capacity - Lan, Nguyen Thi Huong (International research journal of management, IT and social sciences, 2022)
In order to perform well the organization of experiential activities for students of primary schools in Thuy Nguyen district, Hai Phong city in the direction of approaching the capacity, primary schools in the district have been invested and created favorable conditions for education. however, there are certain limitations as well. The results of the survey on the actual situation of experiential activities for students in primary schools in Thuy Nguyen district, Hai Phong city in the direction of competency approach are the basis for proposing measures to manage experiential activities in the direction of competency approach. , along with the requirement of renovating school administration in order to effectively implement the 2018 National Education Program, contributing to improving the quality of comprehensive education.